D’une querelle l’autre : l’autonomisation de la littérature acadienne - Doyon-Gosselin, Benoit; Bélanger, David (Romanica Silesiana)
This article will look at the history of Acadian literature through different disputes within this cultural community. Acadian literature was developed in a homogenous community with a relatively small population, and seems to have grown because of all the disputes. In Acadie, the debate was conducted in newspapers. The article analyses three disputes: 1) the Old against the modern (1963); 2) the chiac dispute (1974—1975) and 3) the France-Acadie price controversy (1995). Key words: Acadian Literature, Empowerment, Dispute, Sociology.